Temporary and Tactical Urbanism in Australia: Perspectives from Practice. Issue 3 (3rd July 2021) - Stevens, Quentin; Awepuga, Fauster; Dovey, Kim
ABSTRACT: "Temporary" and "tactical" (T/T) urbanism is argued to herald a more agile future for urban design and planning, enhancing urban intensity, community engagement, innovation, resilience and local identity. Drawing on interviews with expert practitioners, this paper explores the distinctive character of Australian "T/T" urbanism approaches. It examines their diverse, dynamic assemblages of actors and interests, and their links to neoliberal deregulation, austerity, gentrification, and to long-term state planning and investment. While Australian T/T urbanism follows overseas precedents, it is seen less as a"DIY" or "guerrilla" response to neoliberal regimes, and more focussed on enhancing citizen engagement and collaboration within planning.